TEST OF THE EFFECTIVENESS OF BATAK ONION (ALLIUM CHINENSE G. DON.) ETHANOL EXTRACT ON CREATININE AND UREUM LEVELS OF WHITE RATS (RATTUS NORVEGICUS) INDUCED BY ETHYLENE GLYCOL - Muhammad Gafra Shafa Harahap; Ibnu Hafiz; Mhd Bayu Azhari (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
The kidneys are excretory organs whose function is to remove metabolic waste in the form of toxic substances from the body. Ethylene glycol is a chemical that if consumed in the body can cause damage to the kidneys. Batak onion (Allium chinense G. Don.) is a herbal plant and food typical of North Sumatra which is believed to have health benefits for the body. The aim of this research was to determine the effect of Batak onion ethanol extract on creatinine and urea levels of white rats induced by ethylene glycol. This research used a Completely Randomized Design (CRD) with 25 white rats divided into 5 treatment groups, namely the negative control group was given food and drink, the positive control was induced by 0.75% ethylene glycol, treatment 1 was induced by 0.75% ethylene glycol and extract. Batak onion ethanol was 250 mg/kg BW, treatment 2 was induced by 0.75% ethylene glycol and Batak onion ethanol extract was 500 mg/kg BW and treatment 3 was induced by 0.75% ethylene glycol and Batak onion ethanol extract was 750 mg/kg BW. The data obtained was analyzed statistically using one way Anova with Duncan's follow-up test. The results obtained by Batak onion ethanol extract had an effect on creatinine levels (p = 0.000) and urea levels (p = 0.000) in white mice. Giving Batak onion ethanol extract at a dose of 750 mg/kg BW and ethylene glycol for 30 days was the most effective dose in reducing creatinine and urea levels in white rats.